A Study To Assess The Effectiveness Of Structured Teaching Programme On Knowledge And Attitude Regarding Legal Aspects Of Organ Donation Among Staff Nurses In Critical Care And Emergency Units In Selected North India Hospitals (Journal of Pharmaceutical Negative Results, 2023)
This paper talks about the effectiveness of structured teaching programme on knowledge and attitude regarding legal aspects of organ donation among staff nurses in critical care and emergency units in selected hospitals of Gwalior, MP. The objectives of the study were to assess the effectiveness of Structured Teaching Programme on knowledge and attitude regarding legal aspects of organ donation among staff nurses in critical care and emergency units, and to find out the correlation between knowledge and attitude regarding legal aspects of organ donation among staff nurses of critical care and emergency units and also to find out the association between knowledge and attitude with selected background variables. The research approach adopted for the study was evaluative approach and the research design adopted was pre-experimental, one group pre-test – post-test design. Structured questionnaire containing 25 items on knowledge and of 15 statements 5 point Likert scale on assessing attitude were used. The findings of the study revealed that the Structured Teaching Programme on knowledge and attitude regarding legal aspects of organ donation was effective and the post test knowledge and attitude score on legal aspects of organ donation was higher than the pretest score. There found a significant association in the knowledge and attitude with previous source of information.